The Correlation of Vocabulary Mastery and Reading Motivation towards Reading Comprehension of the Fifth Grade Students in SDN 3 Tanjung Agung Katibung, Lampung Selatan - Imam Nur Fajeri Fajeri; Surastina Surastina; Joko Sutrisno AB; Galuh Dwi Ajeng (IJLHE: International Journal of Language, Humanities, and Education, 2020)
Reading comprehension is an activity that should be mastered by the students in order to enrich their knowledge. There are several factors that influence students’ reading comprehension. This research aims to know the correlation between vocabulary mastery and reading comprehension. The correlation between motivation and reading comprehension. Therefore, this research also aims to find the correlation between vocabulary mastery, motivation and students’ reading comprehension. This research represents descriptive quantitative research by using correlation method. The result of this research indicates that vocabulary correlates positively with reading comprehension. The motivation correlates positively with reading comprehension. Moreover, this study also finds that there is positive correlation between vocabulary, motivation and students’ reading comprehension. There are several ways that can be used to increase student’s reading comprehension such as; familiarize students to read a lot by understanding the contents of the reading text; creating a conducive learning situation in order to increase students’ motivation in reading. By reading a lot and understanding the reading text, it is hoped that students’ vocabulary mastery will increase.